A Review on the Phytochemical and Pharmacological Activities of Cynometra Species from the Southern Western Ghats - Jacob, Jyothi Cheeran; Nair, Rekha Kesavan (Pharmacognosy Reviews)
The genus Cynometra L., belonging to the tropical legume family Fabaceae (subfamily Detarioideae), includes a diverse group of species found in various tropical regions. Several Cynometra species are well known for their role in traditional medicine, especially in areas where they are part of the native plant life. This review highlights and summarizes scientific research on the chemical composition and pharmacological properties of three species native to the southern Western Ghats-Cynometra travancorica, Cynometra beddomei, and Cynometra bourdillonii. Among them, Cynometra travancorica has been the most extensively studied, while Cynometra bourdillonii remains largely unexplored, with little to no research available. This review highlights the various pharmacological activities of these species, including anti-oxidant, anti-inflammatory, anti-microbial, anti-obesity, anti-estrogenic, anti-tumor, and cytotoxic properties. These insights serve as a valuable resource for further research. Comparative studies can play a key role in identifying Cynometra species with unique chemical compositions and in understanding how differences in their secondary metabolites affect their medicinal properties. However, the therapeutic potential of these species remains largely untapped due to the limited number of studies available. In particular, the lack of in vivo research and clinical trials continues to be a major barrier to fully exploring and validating their pharmacological benefits. This review may assist researchers in exploring the pharmacological properties of Cynometra, potentially leading to new discoveries in drug development.
Keywords: Cynometra; Southern Western Ghats; Phytochemistry; Pharmacognosy